'Thinking About What Might Have Happened: Counterfactual Thinking and Post‐traumatic Stress in Individuals Directly and Indirectly Exposed to the 2011 Oslo Bombing'. Issue 6 (November 2016) - Blix, Ines; Kanten, Alf Børre; Birkeland, Marianne Skogbrott; Solberg, Øivind; Nissen, Alexander; Heir, Trond
Summary: Counterfactual thinking (CFT), that is thinking about what might have happened, is linked to post‐traumatic stress. We studied the relationship between type and frequency of CFT and post‐traumatic stress in a sample of directly (n = 50) and indirectly exposed (n = 50) ministerial employees 4 years after the 2011 Oslo bombing. The results showed that frequency of CFT was associated with levels of post‐traumatic stress, among both directly and indirectly exposed participants. In the directly exposed group, self‐reported frequencies of downward counterfactuals were associated with post‐traumatic stress. A similar trend was found for upward counterfactuals. In the indirectly exposed group, self‐reported frequencies of both upward and downward counterfactuals were associated with higher levels of post‐traumatic stress. These results point to the intriguing possibility that people may not only develop post‐traumatic stress disorder as a result of actual experiences, but also via mental simulations of traumatic events that could have happened. Copyright © 2016 John Wiley & Sons, Ltd.